Diversity, Antimicrobial Action and Structure-Activity Relationship of Buffalo Cathelicidins. - Biswajit Brahma; Mahesh Chandra Patra; Satyanagalakshmi Karri; Meenu Chopra; Purusottam Mishra; Bidhan Chandra De; Sushil Kumar; Sourav Mahanty; Kiran Thakur; Krishna Mohan Poluri; Tirtha Kumar Datta; Sachinandan De (PLoS ONE)
Cathelicidins are an ancient class of antimicrobial peptides (AMPs) with broad spectrum bactericidal activities. In this study, we investigated the diversity and biological activity of cathelicidins of buffalo, a species known for its disease resistance. A series of new homologs of cathelicidin4 (CATHL4), which were structurally diverse in their antimicrobial domain, was identified in buffalo. AMPs of newly identified buffalo CATHL4s (buCATHL4s) displayed potent antimicrobial activity against selected Gram positive (G+) and Gram negative (G-) bacteria. These peptides were prompt to disrupt the membrane integrity of bacteria and induced specific changes such as blebing, budding, and pore like structure formation on bacterial membrane. The peptides assumed different secondary structure conformations in aqueous and membrane-mimicking environments. Simulation studies suggested that the amphipathic design of buCATHL4 was crucial for water permeation following membrane disruption. A great diversity, broad-spectrum antimicrobial action, and ability to induce an inflammatory response indicated the pleiotropic role of cathelicidins in innate immunity of buffalo. This study suggests short buffalo cathelicidin peptides with potent bactericidal properties and low cytotoxicity have potential translational applications for the development of novel antibiotics and antimicrobial peptidomimetics.